(3GdeYGQa GdjbjfjIs - (3GdedG eMeO Hf eQJVj GdcGTGfjs
(3ChdgG (B:s
(3CeG HYO ajbhd NGOe GdYdhe GdOjfjI hQGUO GdeYGQa GdjbjfjI eMeO Hf eQJVi GdeOYh HeMSf gPG jG ENhGfj egeGJ eYGQa CUhd GdOjf s
(3BNQgG (B:s
(3aEPG cGf jhe GdbjGeI CcedgG HgPg GdQMeI eGFI gPG BNQ GdcdGe aj GdeYGQa hGdMeO ddg XGgQkG hHGWfkG hGdMeO ddg QH GdYGdejf hGdUdGI Ydi eMeO hBdg GdWGgQjf Bejf s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3eUOQ GbJfGA GdCUd (B:s
(3BjI Gddg GdMcje GdYGeI (B- (3GdfLa (B(289) s
Keywords: (3GdJhMjO hGdedd hGdfMds